DC Microgrid Modeling and Energy Storage Placement to Enhance System Stability - (:unkn) unknown (My University, 2013)
The work of this thesis represents a joint venture between the University of Wisconsin-Milwaukee and the University of Wisconsin-Madison. A DC microgrid is selected for the efficiency benefits, lack of reactive power in the system, and ease of connecting to an AC grid. The system modeling relies on physical parameters and industry standard methods for the estimation of loads and lines. An example model is created for the University of Wisconsin - Milwaukee's Campus. Due to the high penetration of renewable energy sources in the example model, system stability is a concern. To help mitigate stability issues, analysis is performed to have the ideal placement of energy storage. The analysis relies heavily on the deep properties of the system such as Eigenvalues and system controllability. Energy storage placement is verified and evaluated with model simulations.
Keywords: DC Microgrid; Distributed Generation; Eigenvalue; Energy Storage; Renewable Energy; Stability